Enhancement of Competitiveness of the Product in the Tourist Business by Health Tourism Marketing Management - Ianeva, Mariana; Tsonev, Nickolay; Vasileva, Maya; Basmadzieva, Stiliyana (Research Papers, 2018)
The actuality of the examined problems is determined by the fact that the Bulgarian tourism is looking for forms of achieving non-seasonality in the tourist supply.The object of research is the health tourism, the subject of analysis is the aspects of marketing management of health tourism in Bulgaria. The thesis is that, by applying marketing management tools, the competitiveness of the product in the tourism business is increased. The purpose of the research is to establish which aspects of marketing management can be applied to introduce innovations in the field of health tourism in order to increase its competitiveness.The purpose of the article is realized through study and validation of basic tasks such as: Clarifying the essence and specificity of marketing management; analyzing the resource capacity and potential of health tourism in Bulgaria; theoretical issues regarding health management; analysis of key aspects such as standardization and certification in health tourism; study and evaluation of specialized sites on health tourism in Bulgaria.The following research methods have also been used to achieve the objectives and tasks: an overview of the theoretical scientific developments; an overview of materials of international and European organizations; an overview of company surveys; empirical study.Main results:(a) Tourism Business Direction - results: the characteristics of marketing management and their application in health tourism have been identified; the potential of health tourism has been determined and the opportunities for its development in Bulgaria are outlined.(b) Product Competitiveness Direction in the Tourist Business in Bulgaria - results: the factors which prove that Bulgaria can be promoted as a health tourism destination for are outlined; innovative approaches have been identified in tourism to develop and implement standardized health products; Recommendations were made on which aspects of marketing management can be applied for introducing innovations in the field of health management.Conclusions:A change is required in the overall management of the health tourism in Bulgaria; implementing innovations in the specialized sites for health tourism is required;Practical consequences:Successful marketing management in tourism can be realized through the application of standardized health products in tourism enterprises.Originality:Currently in Bulgaria the opportunities for health tourism marketing management are still not thoroughly explored as a year-round form of tourism.